Main determinants of physical activity levels in individuals with Parkinson’s disease - Lana, Raquel de Carvalho; Araujo, Lysandra Nogueira de; Cardoso, Francisco; Rodrigues-de-Paula, Fátima (Arquivos de Neuro-Psiquiatria, 2016)
This study analyzed the relationship between patient characteristics, factors associated with Parkinson’s disease (PD), and physical activity level of individuals affected by the disease. Forty-six volunteers with mild-to-moderate idiopathic PD were assessed using sections II/III of the Unified Parkinson’s Disease Rating Scale and their motor functions were classified according to the modified Hoehn and Yahr (HY) scale. Data such as age, disease duration, the Human Activity Profile (HAP), the Fatigue Severity Scale were collected. Lower limb bradykinesia and clinical subtypes of PD were defined. Two models that explained 76% of the variance of the HAP were used. The first comprised age, ability to perform activities of daily living (ADL), and the HY scale; the second comprised age, ability to perform ADL, and lower limb bradykinesia. Possible modifiable factors such as the ability to perform ADL and lower limb bradykinesia were identified as predictors of physical activity level of individuals with PD.
Keywords: Parkinson’s disease; physical activity; bradykinesia; fatigue